Late Antique Philosophical Terminology in Early Kalām: The Polysemous Greek Term atomon and Its Arabic Equivalent juzʾ lā yatajazzaʾ - Wakelnig, Elvira (Journal of Abbasid Studies, 2019)
The Arabic term “a part which is not divided” (juzʾ lā yatajazzaʾ) is standard in later kalām to express the atom, i.e., the smallest entity out of which the bodies of this world are constituted. However, when early kalām doctrines are read with only this atomist meaning of the term in mind, strange claims result, namely that either an individual like ʿAlī or man is an atom. Reading these doctrines in the context of Late Antique philosophy in which the Greek term “undivided” (atomon) is considered as polysemous provides an interpretative tool to make better sense of the early mutakallimūn’s claims.Discussions of the various meanings of atomon first occur in Greek commentaries to Porphyry’s Isagoge from where they are then excerpted and introduced into compilations of definitions and divisions (diareses) of philosophical terms. A detailed survey of the steady development of these discussions in the Greek tradition sheds light on the condensed form in which they appear in philosophical compilations in Greek, Syriac and Arabic. Surviving Arabic compilations not only contain passages on the various meanings of atomon, but also present information on Democritus’s and Epicurus’s doctrines and are thus suggested as a very plausible, hitherto neglected channel of transmission of Greek atomist theories to early kalām.